Grounded Theory and Atlas.ti: Methodological Resources for Educational Research - Daniel San Martín Cantero (Universidad Autónoma de Baja California, 2014)
The research-based practices in education have experienced a lot of changes, specially in the analysis procedures. These changes have been motivated by the irruption of the Grounded Theory in the research-based practice, but also due to the presence of specific softwares for qualitative analysis of data. This situation is not free from questioning and discussion regarding the true contribution of computers in the research of interpretative tradition. Nevertheless, this would be due to the ignorance of the relation between method-software. In this work, the analytical procedures proposed by the Grounded Theory and the possibilities offered by the ATLAS.ti software in order to improve the qualitative analytical practice are presented. The purpose is to contribute for the theoretical-methodological strengthening in the educational research.